Influence of sludge layer properties on the hydraulic behaviour of gravel-based vertical flow constructed wetlands for primary treatment of sewage - Khomenko, Olha; Dotro, Gabriela; Jefferson, Bruce; Coulon, Frederic; Bajón Fernández, Yadira (Elsevier, 2019)
Sludge accumulation on the first stage of French design vertical flow constructed wetlands has been reported to improve treatment performance by favouring even sewage distribution on the beds' surface and increasing water retention time. However, due to its relatively low permeability, sludge layer can restrict the hydraulic capacity of the wetlands, requiring careful consideration of the feeding and resting strategy in order to avoid system ponding. This study aimed to elucidate the impact that sludge layer properties have on its permeability and investigate artificial modifications that could enhance it. A positive impact of increased organic matter content on sludge permeability was observed, with a 3-times permeability increase for a 15 percentage points higher volatile solids content. The opposite effect was observed for total solids, where an increase of 19 percentage points led to a drop of 1.6 × 10−16 m2 on permeability. The impact of different surface modifications on drying kinetics and sludge layer properties was studied as a means to accelerate sludge layer mineralisation. Artificial modifications that modify surface tension of the sludge layer have been proved to achieve greater permeability and faster mineralisation of the sludge, with potential to achieve higher hydraulic acceptance and reduced operational costs (lower sludge accumulation) if implemented in full scale vertical flow constructed wetlands.
Keywords: Mineralisation; Preferential flow pathways; Sludge permeability; Vertical flow constructed wetlands; Organic matter